Synthesis and Post‐Polymerization Modification of Defined Functional Poly(vinyl ether)s. Issue 13 (24th May 2021) - Butzelaar, Andreas J.; Schneider, Sven; Molle, Edgar; Theato, Patrick
Abstract: Living cationic polymerization is known for a good control over chain growth yielding polymers with well‐defined molar mass distributions and low dispersities. However, the practical challenges involved in the synthesis of poly(vinyl ether)s limited suitable post‐polymerization modifications (PPM) via chemoselective click reactions. Herein the successful controlled cationic polymerization of vinyl ethers bearing pendant CC double and C≡C triple bonds using a single‐component initiation under ambient conditions is reported. Furthermore, the PPM via thiol ‐ene/‐ yne and copper (I) ‐ catalyzed alkyne ‐azide cycloaddition reaction of the obtained polymers is successfully realized laying the foundation for the synthesis of unprecedented functional poly(vinyl ether)s. Abstract : Using a single‐component initiation and control agent the successful cationic polymerization of vinyl ethers with functional groups is shown under ambient conditions. Moreover, post‐polymerization modification of the obtained polymers via efficient click chemistry ( thiol ‐ ene /‐ yne and copper (I)‐ catalyzed alkyne‐ azide cycloaddition ) is demonstrated enabling the synthesis of a great variety of functional poly(vinyl ether)s.